2007
DOI: 10.1016/j.ejpain.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pain in older adults: A prevalence study in the Mediterranean region of Catalonia

Abstract: Although information is available about the prevalence of pain in older adults in Anglo-Saxon and Scandinavian countries, very little is known about older adults in other parts of the world. This study reports the prevalence of pain in a randomly selected sample of older adults living in the Mediterranean region of Catalonia. Besides studying the existence of pain at the time of interview, the authors investigated several characteristics of the participants' pain experience: pain onset, number and location of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 31 publications
10
87
2
12
Order By: Relevance
“…When examining the relation between occupation and type of physical activity, in all occupations (with the exception of the student), walking becomes the most common type of activity with values higher than 66% in all cases; statistically we found no significant differences between the distinct activities and occupation groups (p=0.232) (figure 6). Miró et al (2007) confirmed that in a population of older people 94.2% suffered chronic pain. All these data indicate the high prevalence of moderate and intense pain in old people, which has negative repercussions in carrying out the normal activities basic to daily life.…”
Section: Figure 4 Distribution Of Type Of Physical Activity Accordinsupporting
confidence: 69%
“…When examining the relation between occupation and type of physical activity, in all occupations (with the exception of the student), walking becomes the most common type of activity with values higher than 66% in all cases; statistically we found no significant differences between the distinct activities and occupation groups (p=0.232) (figure 6). Miró et al (2007) confirmed that in a population of older people 94.2% suffered chronic pain. All these data indicate the high prevalence of moderate and intense pain in old people, which has negative repercussions in carrying out the normal activities basic to daily life.…”
Section: Figure 4 Distribution Of Type Of Physical Activity Accordinsupporting
confidence: 69%
“…The main finding of this study is that >50% of the geriatric population in nursing homes reported chronic pain, which is in concurrence with previous reports. [16,17] Our results showed that pain severity and intensity increase with increasing age. Similarly, Leong et al, and Brochet et al reported that residents with chronic pain were older than those without pain.…”
Section: Discussionmentioning
confidence: 56%
“…Women in Hong Kong reported more painful sites than men, besides a higher percentage of headaches 6 . Miró et al 34 also found that headache was significantly more common in women. In Spain, headache was more common in women (22.7%) and pain in the lower limbs more common in men (24.1%).…”
Section: Variablesmentioning
confidence: 84%
“…Evidence also suggests that women with chronic pain experience more depression than men 6,18,27,34,36 . Women are more emotional and more readily display their feelings of sadness caused by pain.…”
Section: Variablesmentioning
confidence: 99%